Corporate Governance, Political Connection and Corporate Risk Disclosure: The Case of State-Owned Enterprises in Indonesia - Anggita Langgeng WIJAYA (CECCAR Business Review)

(untitled)
Corporate risk disclosure is one of the strategic issues in efforts to optimize the role of corporate governance in state-owned enterprises in Indonesia. This study will examine the factors that influence the level of corporate risk disclosure in state-owned enterprises in Indonesia, namely corporate governance and political connections. This study uses data from the annual report of state-owned enterprises in Indonesia for 2015-2022. The sampling technique used is purposive sampling. Hypothesis testing in this study uses moderated regression analysis. The results indicate that, in state-owned enterprises in Indonesia, corporate governance has a positive effect on corporate risk disclosure. This research also found that political connections strengthen the influence of corporate governance on corporate risk disclosure. This study implies that if investors want more comprehensive corporate risk disclosure, investors must ensure that management has adequately implemented all corporate governance mechanisms. In implementing good corporate governance, political connections can convince stateowned management to improve the quality and quantity of corporate risk disclosure.